2018
DOI: 10.4274/meandros.36035
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Analysis of Temporomandibular Joint Trabecular Bone Structure in Patients with Rheumatoid Arthritis on Cone Beam Computed Tomography Images

Abstract: Amaç: Bu çalışmanın amacı, romatoid artritli (RA) hastaların konik ışınlı bilgisayarlı tomografi (KIBT) görüntüleri üzerinde temporomandibular eklemin trabeküler kemik yapısındaki değişiklikleri fraktal boyut (FB) analizi ile değerlendirmektir. Gereç ve Yöntemler: Bu çalışmada, patolojik lezyon veya implant tedavi planlaması gibi tanı amacıyla KIBT görüntülemesi yapılan 17 kadın RA hastası ve 16 sağlıklı kadın birey değerlendirildi ve Image J

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
1
1
0
1
Order By: Relevance
“…Both of these findings were consistent with the study conducted by Arsan et al [ 8 ], wherein although the fractal value of the right side in the case group was less compared to the control group, it was not statistically significant and there was a statistically significant difference on the left side supporting the present study. It was also in line with the study conducted by Yesiltepe et al [ 16 ] on patients with rheumatoid arthritis of TMJ in which there was a statistically significant difference between the case and the control group on the right side. Also, the fractal findings were supported by the studies conducted by Gumussoy et al [ 17 ] and Jayachandran et al [ 18 ] done on digital panoramic radiographs in patients with chronic renal failure and rheumatoid arthritis.…”
Section: Discussionsupporting
confidence: 91%
“…Both of these findings were consistent with the study conducted by Arsan et al [ 8 ], wherein although the fractal value of the right side in the case group was less compared to the control group, it was not statistically significant and there was a statistically significant difference on the left side supporting the present study. It was also in line with the study conducted by Yesiltepe et al [ 16 ] on patients with rheumatoid arthritis of TMJ in which there was a statistically significant difference between the case and the control group on the right side. Also, the fractal findings were supported by the studies conducted by Gumussoy et al [ 17 ] and Jayachandran et al [ 18 ] done on digital panoramic radiographs in patients with chronic renal failure and rheumatoid arthritis.…”
Section: Discussionsupporting
confidence: 91%
“…The FA method has been used in previous studies for the analysis of trabecular microstructure in periodontal disease, osteoporosis, and implant planning. 20 23 In a study-related periodontitis and alveolar bone loss, Updike and Nowzari 8 reported that the destructive effects of periodontitis on trabecular bone may be successfully evaluated with FA method. Jett et al 24 stated that even small destructive changes on trabecular bone in the early stages of pathology may be determined by the FA method before the effects of periodontal destruction are emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Araştırmacılar bu hastalıkların kemik kalitesi üzerindeki olumsuz etkileri ve bunların erken teşhisiyle ilgili bir hayli çalışma yapmıştır. [4][5][6][7][8][9] Kemik kalitesi; trabeküler devamlılık, kemik geometrisi, kemikte oluşmuş olan mikrohasarlar, kemik dokunun mimarisi, mineralizasyon miktarı ve kusurları gibi birçok faktöre bağlıdır. Kemik yapının analizinde geçmiş yıllarda sıklıkla kemik mineral yoğunluğu ölçümü kullanılmaktaydı.…”
Section: Introductionunclassified